Circulating (Poly)phenol Metabolites - Carecho, Rafael (2022)
Funding Information: This work was supported by European Research Council (ERC) under the European Union's Horizon 2020 research and innovation program under grant agreement No. 804229; iNOVA4Health – UIDB/04462/2020 and UIDP/04462/2020, a program financially supported by Fundação para a Ciência e Tecnologia (FCT)/Ministério da Ciência, Tecnologia e Ensino Superior (MCTES), through national funds. FCT/MCTES, through the project PTDC/BTM‐ORG/29580/2017. Authors would like to acknowledge FCT for financial support of R.C. (PD/BD/135492/2018) and J.G.‐P. (SFRH/BD/145522/2019). M.L. was supported by the Land‐BW (NAM‐ACCEPT) and funding by the European Union's Horizon 2020 research and innovation program under grant agreements No. 964537 (RISK‐HUNT3R), No. 964518 (ToxFree), and No. 825759 (ENDpoiNTs). Publisher Copyright: © 2022 The Authors. Molecular Nutrition & Food Research published by Wiley-VCH GmbH